The Poetics of Silence: Reimagining Voice and Absence in Contemporary Women’s Writing - Dr. Dinesh Kumar Verma; Dr. Asha Verma (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This paper explores the dialectic of voice and silence in contemporary women’s writing, analysing how selected texts by Margaret Atwood, Arundhati Roy, and Chimamanda Ngozi Adichie reimagine silence as a site of resistance and self-definition. Grounded in feminist and poststructuralist theory (Cixous, Irigaray, Spivak), the study situates silence within the historical discourse of female oppression and reinterprets it as a strategy of empowerment. Through comparative textual analysis, the research demonstrates that silence in women’s narratives functions not as void but as creative agency, mediating trauma, identity, and cultural displacement. The findings suggest that silence possesses its own rhetorical power—constructing alternative modes of expression that challenge patriarchal discourse and expand the boundaries of feminist poetics. Ultimately, the paper argues that to be silent is not to be voiceless, but to reimagine what voice can mean.